Severe B cell hyperplasia and autoimmune disease in TALL-1 transgenic mice - Khare, Sanjay D. (The National Academy of Sciences, 2000)
TALL-1/Blys/BAFF is a member of the tumor necrosis factor (TNF) ligand superfamily that is functionally involved in B cell proliferation. Here, we describe B cell hyperplasia and autoimmune lupus-like changes in transgenic mice expressing TALL-1 under the control of a β-actin promoter. The TALL-1 transgenic mice showed severe enlargement of spleen, lymph nodes, and Peyer's patches because of an increased number of B220+ cells. The transgenic mice also had hypergammaglobulinemia contributed by elevations of serum IgM, IgG, IgA, and IgE. In addition, a phenotype similar to autoimmune lupus-like disease was also seen in TALL-1 transgenic mice, characterized by the presence of autoantibodies to nuclear antigens and immune complex deposits in the kidney. Prolonged survival and hyperactivity of transgenic B cells may contribute to the autoimmune lupus-like phenotype in these animals. Our studies further confirm TALL-1 as a stimulator of B cells that affect Ig production. Thus, TALL-1 may be a primary mediator in B cell-associated autoimmune diseases.